2012
DOI: 10.1017/s1751731111002382
|View full text |Cite
|
Sign up to set email alerts
|

Responses of growth performance and tryptophan metabolism to oxidative stress induced by diquat in weaned pigs

Abstract: During many pathological conditions, the tryptophan concentration in blood may be reduced. However, the effects of oxidative stress on tryptophan metabolism remain unknown. In this study, we investigated the effects of oxidative stress on growth performance and tryptophan metabolism in weaned pigs. A total of 24 weaned pigs were assigned to one of three treatments that included pigs fed ad libitum (control), pigs challenged with diquat at a dose of 10 mg/kg BW and fed ad libitum (oxidative stress) or pigs pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 31 publications
(32 reference statements)
6
56
0
1
Order By: Relevance
“…Diquat has been reported to impair growth performance and nutrient utilization [18, 19]. The reduced gut morphology and growth performance by diquat challenge in the present are in agreement with published report [28].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Diquat has been reported to impair growth performance and nutrient utilization [18, 19]. The reduced gut morphology and growth performance by diquat challenge in the present are in agreement with published report [28].…”
Section: Discussionsupporting
confidence: 93%
“…This is mainly due the disruption in the oxidative balance [18], which is evidenced by the decrease in serum concentrations of SOD, GSH-Px, CAT, T-AOC, and GSH after exposure to diquat injection in piglets of basal diet treatments. In the previous studies, diquat has been demonstrated to increase serum MDA concentration but also to inhibit the activities of SOD and GSH-Px [18, 19]. In addition, the present results of serum cytokine concentrations, intestinal histopathological grading, and MPO activity indicated that diquat evaluates the inflammatory response of weaned pigs, which is consistent with previous research [9, 28, 29].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations